IMPLEMENTATION OF THE LARAVEL FRAMEWORK TO BUILD A WEBSITE-BASED SPP BILLING APPLICATION - Ricky Ramadhan Harahap; Barany Fachri (INFOKUM, 2022)
In the current technological developments that are increasingly advanced, data processing can be operated effectively and efficiently. Processing data manually can take a long time and will get errors in the process. Currently at SMK Negeri 9 Medan in making payments or viewing spp bills it is still manual by looking at notes or spp billing cards. The obstacle experienced was removing the card and it was quickly damaged. To overcome this problem, it is necessary to have a website system in managing spp payments. Besides that, it can also speed up the preparation of SPP arrears payment reports and store payments securely so as to make reports more accurate. To build this system using the PHP Programming Language and database storage using MySql. From the results of this study it can be expected to help the school in making transactions in paying SPP.